THE ETHICAL DILEMMA OF VILLAGE OFFICIALS: FRAUD IN THE DISTRIBUTION OF DIRECT CASH ASSISTANCE - Ismail, Mahmud; Haryadi, Bambang; Prasetyono, Prasetyono (Assets: Jurnal Akuntansi dan Pendidikan, 2023)
ABSTRACTThe purpose of this research is to reveal the ethical dilemma of the role of village officials in the fraudulent practice of distributing Village Fund Direct Cash Assistance (BLT-DD). This research uses a phenomenological approach. The study showed that village officials experienced an ethical dilemma regarding fraud in distributing BLT-DD. First, the village head experienced a dilemma between his residents' demand that the BLT-DD program be divided equally so that because of the sympathy felt by the village head, the BLT-DD money was cut. Second, the village secretary must face the village head’s orders to manipulate signatures. Third, the Village Consultative Board felt uncomfortable wanting to monitor the performance of the village head. Fourth, there is a lack of clarity in the structure of the BLT-DD volunteer team, so they experience confusion in carrying out their duties in the BLT-DD program. Fifth, the experience gained becomes a solution to overcoming the dilemma experienced by the actor in the fraudulent practice of distributing BLT-DD.ABSTRAKTujuan penelitian ini menyingkap dilema etis peran perangkat desa pada praktik fraud penyaluran Bantuan Langsung Tunai Dana Desa (BLT-DD). Penelitian ini mengggunakan pendekatan fenomenologi. Hasil penelitian menunjukkan bahwa perangkat desa mengalami dilema etis atas fraud yang dilakukan pada penyaluran BLT-DD. Pertama, kepala desa mengalami dilema antara permintaan warganya atas program BLT-DD harus dibagi rata, sehingga atas rasa simpati yang dialami kepala desa maka uang BLT-DD dipotong. Kedua, sekretaris desa harus menghadapi perintah kepala desa untuk manipulasi tandatangan. Ketiga, Badan Permusyawaratan Desa mengalami rasa tidak enak hati yang ingin mengawasi kinerja kepala desa. Keempat, adanya ketidak jelasan struktur tim relawan BLT-DD, sehingga mereka mengalami kebingungan untuk menjalankan tugasnya pada program BLT-DD. Kelima, Pengalaman yang diperoleh menjadi solusi dalam mengatasi rasa dilema yang dialami sang aktor pada praktik fraud penyaluran BLT-DD.